2011
DOI: 10.3892/ol.2011.455
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of hematopoietic stem cells and the effect of CD38 expression during the early erythroid progenitor cell development process

Abstract: Abstract. The aim of this study was to investigate changes in primitive hematopoietic cells through CD38 expression, identify the stage at which erythrocyte differentiation CD38 gains activity and the effects of serum factors on this expression by establishing a hematopoietic stem cell system in the erythroid development process. Using an immunomagnetic labeling and separation technique, CD34 + cells were selected from cord blood. The CD34 + cells were cultured in a 2 mM L-glutamine-enriched medium containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…In our study, when examining EPO and renin levels that were decreased in Group I/R, EPO level did not show any significant change, but renin level was significantly increased especially in the groups treated with 8‐Br‐cADPR. Previous studies have reported that there was a positive correlation between CD38 and EPO, and that this contributed to progenitor cell formation (Albeniz, Turker‐Sener, Bas, Kalelioglu, & Nurten, ; Todosenko et al, ). Xiong et al () reported that the CD38/cADPR signaling pathway may contribute to the regulation of renin release.…”
Section: Discussionmentioning
confidence: 90%
“…In our study, when examining EPO and renin levels that were decreased in Group I/R, EPO level did not show any significant change, but renin level was significantly increased especially in the groups treated with 8‐Br‐cADPR. Previous studies have reported that there was a positive correlation between CD38 and EPO, and that this contributed to progenitor cell formation (Albeniz, Turker‐Sener, Bas, Kalelioglu, & Nurten, ; Todosenko et al, ). Xiong et al () reported that the CD38/cADPR signaling pathway may contribute to the regulation of renin release.…”
Section: Discussionmentioning
confidence: 90%
“…CD38 is a type II membrane surface glycoprotein expressed on a variety of mature hematopoietic cells. CD38 expression is either low or absent on early HSPC populations and most definitions of the primitive, pluripotent human HSCs are contained within the CD34 + /CD38 − fraction . CD34 + /CD38 − cells comprise only ∼1%–3% of CD34 + cells and thus are 50–100 times more enriched for HSPC than the unfractionated CD34 + population.…”
Section: Introductionmentioning
confidence: 99%
“…The change in CD38 expression was ranked as the second-most significant change and CD93 as the twelfth-most significant change by differential gene expression analysis with DEseq [98]. Interestingly, the CD38 and CD93 expression levels are important biomarkers for leukemia cell immunophenotype: CD34 + CD38 − cells are a primitive sub-population of progenitor cells which are generally highly quiescent [107], while the cell surface lectin CD93 is expressed on a sub-population of these cells, identifying them as predominantly cycling, non-quiescent leukemia-initiating cells [108]. Therefore, the changes in CD38 and CD93 RNA expression exhibited by molm-13 R2 cells are consistent with a phenotypic shift toward a more stem-like quiescent cell.…”
Section: Discussionmentioning
confidence: 99%